Association between meal skipping and the double burden of malnutrition among university students - Olagunju, Mobolaji; Aleru, Elizabeth Oluwafolakemi; Abodunrin, Olunike Rebecca; Adedini, Comfort Busola; Ola, Oluwabukola Mary; Abel, Chukwuemeka; Adewole, Ifeoluwa Eunice; Okunbor, Hilary Nosa; Akinsolu, Folahanmi Tomiwa (The North African Journal of Food and Nutrition Research, 2024)
Background: The study delves into the nuanced relationship between meal skipping and the double burden of malnutrition among university students. It addresses a critical gap in understanding how young adults' irregular dietary patterns contribute to undernutrition and overnutrition, phenomena typically studied in isolation.Aims: This research aimed to shed light on the broader implications of meal skipping within the context of student health and well-being.Subjects and Methods: The study surveyed a representative sample of undergraduate students from various academic disciplines at Lead City University in Ibadan, Nigeria, utilizing a descriptive cross-sectional approach. Detailed questionnaires were administered to assess the frequency of meal skipping, dietary habits, and associated lifestyle factors. Body mass index (BMI) and self-reported health data were also collected. Statistical analyses, including univariate and bivariate analysis, were employed to identify the nutritional status and meal patterns of the students, Principal component analysis was employed to identify the dietary patterns prevalent among the students from the food frequency questionnaire administered.Results: The findings reveal a significant correlation between meal skipping and the risk of undernutrition and overnutrition. Students who regularly skip meals are likely at an increased risk of undernutrition, characterized by lower BMI and potential micronutrient deficiencies, and overnutrition, indicated by higher BMI and associated health risks. This dual risk factor challenges existing perceptions of nutrition among young adults, suggesting that meal skipping can be a critical determinant of diverse and complex nutritional outcomes.Conclusion: The study highlights the urgent need for comprehensive nutritional strategies at university campuses, focusing on educating students about the risks associated with inconsistent eating patterns. It calls for implementing targeted interventions and policy changes to address the double burden of malnutrition, promoting healthier lifestyles, and preventing long-term health issues among university students.Keywords: Meal Skipping, Double Burden of Malnutrition, University Students, Nutritional Status, Dietary Patterns, Public Health Interventions, Young Adult Health.